“Tourist service based on outdoor activities at the spirit of the mountain viewpoint.” - Carranza Martínez, Rubidia Yamileth; Vásquez Chiquillo, Carolina Isabel (Universidad de El SalvadoR. Facultad de Ciencias y Humanidades., 2025)
Disponible en soporte impreso.